2009
DOI: 10.1021/nn900214g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Structural Analysis of Carbon-Supported Co Core/Pt Shell Electrocatalysts Using Electroless Deposition Methods

Abstract: Cobalt core/platinum shell nanoparticles were prepared by the electroless deposition (ED) of Pt on carbon-supported cobalt catalyst (Co/C) and verified by HRTEM images. For a 2.0 wt % Co/C core, the ED technique permitted the Pt loading to be adjusted to obtain a series of bimetallic compositions with varying numbers of monolayers (ML). The tendency for corrosion of Co and the electrochemical (i.e., oxygen reduction reaction (ORR)) activity of the structures were measured. The results from temperature-programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 83 publications
(95 reference statements)
0
71
0
3
Order By: Relevance
“…The extent of this effect depends on the size of the particle as well as its constituting elements and thus probably requires increased attention from the experimental side. On the other hand, Fe-Pt and Co-Pt nanoparticles with a Pt-enriched surface may be of use for catalytic purposes [76,77] taking advantage of their magnetism as another degree of freedom for further manipulation. Indeed, such bimetallic core-shell structures receive increased attention as they provide new opportunities to optimize their functional properties [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…The extent of this effect depends on the size of the particle as well as its constituting elements and thus probably requires increased attention from the experimental side. On the other hand, Fe-Pt and Co-Pt nanoparticles with a Pt-enriched surface may be of use for catalytic purposes [76,77] taking advantage of their magnetism as another degree of freedom for further manipulation. Indeed, such bimetallic core-shell structures receive increased attention as they provide new opportunities to optimize their functional properties [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…Here, "large" Co cores (> 10 nm) tend to cause aggregated Pt depositions (e.g., non-continuous 3D Pt structures), whereas "small" Co cores (< 6 nm) tend to provide layer-by-layer growth, implying that the catalytic activity of Co@Pt differs with differing core sizes. And because non-continuous Pt shells lead to the quick corrosion of Co in 0.3 M H 2 SO 4 [472], the thickness of the shell greatly affects the catalytic activity of core-shell Co@Pt samples, with the monolayer Pt shell over Co core yielding the highest ORR activity [472].…”
Section: Co As Corementioning
confidence: 99%
“…And because of this, parts of the Pt atoms will exhibit similar characteristics to pure Pt, which limits Pt catalytic activity. In addition, non-continuous Pt shells will lead to the corrosion of the 3d metal cores [462,464,472]. 2.…”
Section: Merits and Demerits Of Non-noble Monometallic Coresmentioning
confidence: 99%
“…The formation of alloy phase in the Pt-Co/C samples is not an expected result of the electroless deposition process. Platinum was intended to deposit as a shell over the cobalt seed particles as prior studies have shown for transition metals [17,[21][22][23]39], particularly on cobalt [20]. It is possible that the substitution of cobalt into the platinum lattice to form a Pt-Co alloy structure may be due to the simultaneous action of GD with ED, particularly the rapid ED kinetics resulting from the high initial Representative HAADF-STEM images of the samples with the lowest (Sample A) and highest (Sample D) loadings of Pt are shown in Figure 9.…”
Section: Xrd Haadf-stem and Xeds Characterization Of Pt-co/c Catalystsmentioning
confidence: 99%
“…The electroless developer bath used for the deposition of platinum was based on previous work by Beard et al [20][21][22], with the modification of substituting citrate for ethylenediamine (EN) as a stabilizing and chelating agent for Pt 4+ [23]. For the ED experiments, the aqueous bath was maintained at pH 10 and chloroplatinic acid (H 2 PtCl 6 ) used as the Pt source (existing as [PtCl 6 ] 2´c omplex in basic solution) and dimethylamine borane ((CH 3 ) 2 NH¨BH 3 , DMAB) as the reducing agent.…”
Section: Electroless Deposition Of Ptmentioning
confidence: 99%